Antibacterial Effectiveness of Lemon (Citrus limon (L.) Osbeck) Peel Extract against Porphyromonas gingivalis - Azkya D. M. Latupeirissa; Calvin Kurnia; Vinna K. Sugiaman (Universitas Sam Ratulangi, 2022)
Abstract: Periodontitis is an inflammatory disease caused by microorganisms resulting in progres-sive damage of periodontal tissue. One of the main pathogens is Porphyromonas gingivalis. Periodontal disease can be treated with antibiotics but they have side effects and cause bacterial resistance. Herbal plants that can be used as alternative medicine, inter alia, lemon peel (Citrus limon (L.) Osbeck). Its active compounds such as flavonoids, tannins, steroids, and triterpenoids have antibacterial effects. This study aimed to determine the antibacterial effectiveness of the ethanolic extract of lemon peel (Citrus limon (L.) Osbeck) against Porphyromonas gingivalis in several concentrations of 0.625%, 1.25%, 2.5%, 5%, and 10%.Â The method used in this study was the broth microdilution test to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) based on the Clinical and Laboratory Standards Institute (CLSI). The results showed that MIC was at a concentration of 2.5% with an inhibition result of 75.80% and MBC at a concentration of 10% with an inhibition result of 99.53%. In conclusion, lemon peel extract (Citrus limon (L.) Osbeck) had antibacterial effectiveness against Porphyromonas gingivalis.Keywords: lemon peel extract (Citrus limon (L.) Osbeck; periodontitis; Porphyromonas gingivalisÂ Abstrak: Periodontitis merupakan penyakit inflamasi yang disebabkan oleh mikroorganisme sehingga terjadinya kerusakan progresif pada jaringan periodontal. Salah satu patogen utama ialah Porphyromonas gingivalis. Penyakit periodontal dapat diobati dengan antibiotik namun memiliki efek samping dan resistensi bakteri. Tumbuhan herbal yang dapat digunakan sebagai pengobatan alternatif ialah kulit jeruk lemon (Citrus limon (L.) Osbeck) yang memiliki senyawa aktif seperti flavonoid, tanin, steroid dan triterpenoid yang mengandung efek antibakteri. Penelitian ini bertujuan untuk mengetahui efektivitas antibakteri ekstrak etanol kulit jeruk lemon (Citrus limon (L.) Osbeck) terhadap Porphyromonas gingivalis pada konsentrasi 0,625%, 1,25%, 2,5%, 5%, dan 10%. Metode yang digunakan ialah uji broth microdilution untuk menentukan konsentrasi hambat minimum (KHM) dan konsentrasi bunuh minimum (KBM) berdasarkan Clinical and Laboratory Standards Institute (CLSI). Hasil penelitian pada berbagai konsentrasi yang diujikan menunjukkan bahwa KHM berada pada konsentrasi 2,5% dengan hasil inhibisi 75,80% dan KBM pada konsentrasi 10% dengan hasil inhibisi 99,53%. Simpulan penelitian ini ialah ekstrak kulit jeruk lemon (Citrus limon (L.) Osbeck) memiliki efektivitas antibakteri terhadap Porphyromonas gingivalis.Kata kunci: ekstrak kulit jeruk lemon (Citrus limon (L.) Osbeck; periodontitis; Porphyromonas gingivalis